2005
DOI: 10.21273/hortsci.40.5.1524
|View full text |Cite
|
Sign up to set email alerts
|

Growth Response of Container-grown Pin Oak and Japanese Maple Seedlings to Sulfur Fertilization

Abstract: Sulfur (S) is essential to the growth of higher plants; however, research on S fertilizer requirements for container-grown nursery tree species has not been established. The purpose of this study was to determine the substrate solution S concentration that maximizes the growth of container-grown pin oak (Quercus palustris Münchh) (pin oak–K2SO4 experiment) and japanese maple (Acer palmatum Thunb.) (japanese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…S is essential to the growth of higher plants (Browder et al 2005). S availability is also partly related to soil moisture such as observed in rainfall gradients in tropical areas of Africa (Itanna 2005).…”
Section: Introductionmentioning
confidence: 99%
“…S is essential to the growth of higher plants (Browder et al 2005). S availability is also partly related to soil moisture such as observed in rainfall gradients in tropical areas of Africa (Itanna 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes S can improve growth even when a change in pH is not needed. Applying solutions (containing KCl and K2SO4) to pH 4.1 pine bark medium demonstrated that growth of oak and maple in containers was related to the amount of sulfur added (Browder et al 2005). Likewise, 100 kg ha -1 of S increased the growth of container-grown quaking aspen growing in pH 5.5 soil (Liang and Chang 2004).…”
Section: Sulfurmentioning
confidence: 98%
“…Although fertilizing with N plus K can increase root-collar diameter of slash pine (Mead and Pritchett 1971), there are no data from nurseries to show K fertilization increases the root-collar diameter of pine seedlings (Westveld 1946;Steinbeck 1962;Hodgson 1977;Hinesley and Maki 1980;South and Donald 2002). When biomass is increased with K2SO4 fertilization (Hodgson 1977;McKee 1978;Browder et al 2005b), the growth increase might be due to correcting a S deficiency (Lyle and Pearce 1968;Will and Youngberg 1978;Browder et al 2005b). Perhaps some researchers incorrectly assumed that K increased growth when a S deficiency was corrected by a K2SO4 treatment.…”
Section: Will K Fertilization Increase Growth Of B Areroot Seedlingsmentioning
confidence: 99%
“…For hardwoods, K fertilization will sometimes increase growth when roots are in water (Murphy and McAdoo 1969;Houman et al 1990) or when seedlings are grown in pots containing sand (Rosendahl 1943;Browder et al 2005b;Foulger et al 2007;Whittier 2018). In contrast, K fertilization typically has no positive effect on hardwoods when soil contains some silt and clay.…”
Section: Will K Fertilization Increase Growth Of B Areroot Seedlingsmentioning
confidence: 99%
See 1 more Smart Citation